The Role of Emotions in the Practicum Experience of Ecuadorian Pre-Service English Teachers - Macías Sánchez, Karla Nohelia; Coutinho dos Santos, Jardel (Arandu UTIC, 2025)
This study explores the emotional experiences of EFL pre service teachers in Ecuador during their professional practice, emphasizing the importance of emotional intelligence (EI) and emotional support in their development. Using a mixed-method approach, it combines a quantitative method (survey) and two qualitative methods (interviews and visual narratives such as memes) to understand how emotions affect their performance, motivation, and professional identity formation. The results show that students face a variety of emotions, both pleasant and unpleasant, related to pedagogical challenges, uncertainty, and pressure, aspects that can influence their well-being and teaching effectiveness. The research shows that developing EI is key to managing these emotions, reducing stress, and strengthening resilience, aspects that are limited by the lack of emotional support spaces in internships. In addition, it reflects the necessity to incorporate strategies such as peer support, creative reflective activities, and training in social-emotional skills into teacher training programs.